Fungi (S) - Johannes Lundberg (Swedish Museum of Natural History, 2010)
This database contains information on the fungi specimens registered so far in the herbarium of the Swedish Museum of Natural History. The fungi collection, the fungarium, consists of approximately 32,000 species and 370,000 objects, apart from the lichenized (lichen-forming) fungi, which are kept in a separate collection. Important collectors are Giacomo Bresadola, Paul Dietel, Paul Hennings, Nils Lundqvist, Heinrich Rehm, Lars Romell and Paul and Hans Sydow
Keywords: Occurrence; Specimen; Occurrence; OCCURRENCE; Biological Sciences; Biologi